Enhancing Electricity Production in Photovoltaic Systems Using a Double-Axis Solar Tracker - Nugraha, Muhammad Adjie; Asnil (Journal of Industrial Automation and Electrical Engineering, 2025)
The global energy crisis, still heavily reliant on fossil fuels, drives the need for innovations in renewable energy utilization, particularly solar energy. Indonesia, with abundant solar energy potential, has a significant opportunity to enhance solar energy usage through solar tracking technology. This study aims to design and test an Arduino-based double axis solar tracker system that improves solar energy absorption efficiency. The system uses an Arduino Mega 2560 as the main controller, equipped with Light Dependent Resistor (LDR) sensors and other supporting sensors to optimize the solar panel’s position. Testing was conducted under three weather conditions: sunny, partly cloudy, and overcast, to compare the performance of the double axis system with single axis and fixed panels. The results indicate that the double axis solar tracker system produced the highest power output under all weather conditions, especially on sunny days, with an increase in power efficiency of up to 30-35% compared to fixed panels. This technology provides an efficient and economical solution for Indonesia to maximize solar energy utilization, supporting national renewable energy targets.